2021
DOI: 10.35699/1983-3652.2021.33027
|View full text |Cite
|
Sign up to set email alerts
|

Aplicaciones que emplean y recomendaciones que entregan las y los docentes universitarios para la autorregulación del aprendizaje en contexto de la pandemia por COVID-19

Abstract: El uso estratégico de las aplicaciones digitales en educación superior adquiere especial relevancia en tiempos de pandemia por COVID-19. Se presenta un estudio exploratorio en el cual se indaga en el uso de aplicaciones digitales y las que recomiendan docentes universitarios para la autorregulación del aprendizaje en contexto de enseñanza virtual, por COVID-19. La metodología fue de carácter cualitativa, con un enfoque fenomenográfico, basado en tres grupos focales, con una muestra intencional de 17 docentes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
1
0
6
Order By: Relevance
“…Mentimeter, Quizziz) can encourage the achievement of more specific participatory objectives than the gamified games themselves, but here it has been revealed that the companion of phases D and S in the methodology from the use of the elements of the video game have acted as a dissipator of the cognitive recharge in each area of learning. This was determined by other investigations that reveal that the playful power of these factors can be elemental to obtain greater attraction and sustained attention without the need for the game to present a learning objective, more only a personal leisure objective [6]- [8].…”
Section: Comparison In the Mathematical Science And Communication Var...mentioning
confidence: 99%
“…Mentimeter, Quizziz) can encourage the achievement of more specific participatory objectives than the gamified games themselves, but here it has been revealed that the companion of phases D and S in the methodology from the use of the elements of the video game have acted as a dissipator of the cognitive recharge in each area of learning. This was determined by other investigations that reveal that the playful power of these factors can be elemental to obtain greater attraction and sustained attention without the need for the game to present a learning objective, more only a personal leisure objective [6]- [8].…”
Section: Comparison In the Mathematical Science And Communication Var...mentioning
confidence: 99%
“…A raíz de la pandemia por la COVID-19, la implementación de estrategias para la mejora del aprendizaje en línea se ha acelerado. En una investigación exploratoria realizada por Infante et al (2021) se indagó sobre el uso de aplicaciones digitales en la docencia universitaria para la promoción de la autorregulación del aprendiza-je en línea. Los autores identificaron 27 aplicaciones empleadas por los docentes que tenían relevancia para facilitar la autorregulación del aprendizaje.…”
Section: Fomento De La Autorregulación Y La Metacognición a Través De...unclassified
“…No en vano, el mundo digital tiene coincidencias y concomitancias con competencias tradicionales (lectoescritura, habilidades matemáticas) y competencias relacionadas con medios de información (recursos multimedia, hipertextuales, digitales, etc.) (Infante-Villagrán et al, 2021).…”
Section: Introductionunclassified